2010
DOI: 10.1021/jf903883e
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Anthocyanins in Yard-Long Beans (Vigna unguiculata ssp. sesquipedalis L.) by High-Performance Liquid Chromatography with Diode Array Detection and Electrospray Ionization/Mass Spectrometry (HPLC−DAD−ESI/MS) Analysis

Abstract: Anthocyanins play an important role in physiological functions related to human health. The objective of this study was to investigate the profiles of anthocyanins in the immature purple pods and black seeds of yard-long beans ( Vigna unguiculata ssp. sesquipedalis L.) using high-performance liquid chromatography (HPLC) with diode array detection and electrospray ionization/mass spectrometry (DAD-ESI/MS) analysis. The individual anthocyanins were identified by comparing their mass spectrometric data and retent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 17 publications
4
26
0
2
Order By: Relevance
“…Anthocyanin was analyzed by using a high performance liquid chromatography (HPLC) method (Ha et al 2010). Freezedried fresh or wine seed powder (0.5 g) was extracted with 10 mL of 40 % methanol (0.1 % HCl) for 48 h at 4°C in the dark and filtration was performed using a 0.45 μm cellulose acetate syringe filter (Millipore, Billerica, MA, USA) prior to injection.…”
Section: Identification and Quantification Of Anthocyaninsmentioning
confidence: 99%
“…Anthocyanin was analyzed by using a high performance liquid chromatography (HPLC) method (Ha et al 2010). Freezedried fresh or wine seed powder (0.5 g) was extracted with 10 mL of 40 % methanol (0.1 % HCl) for 48 h at 4°C in the dark and filtration was performed using a 0.45 μm cellulose acetate syringe filter (Millipore, Billerica, MA, USA) prior to injection.…”
Section: Identification and Quantification Of Anthocyaninsmentioning
confidence: 99%
“…Nine natural anthocyanins, including the six found by Korean researchers, and three other major ones such as cyanidin-3-O-glucoside (C3G), delphinidin-3-O-glucoside (D3G), and petunidin-3-O-glucoside (P3G) are present in the testa of black soybean (Lee et al, 2009). Although the total anthocyanin content depends on the types and sources of the soybean and ranges between 3 and 18 mg/g in 14 types of black soybean testa, the Cheongja #3 types of black soybean contains seven anthocyanins, with dominant levels of C3G, D3G and P3G (Ha et al, 2010). Especially, 65% of the total anthocyanins in black soybean testa is composed of C3G, and 25% of them is D3G (Lee et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al (2004) categorized a wide array of foods in terms of antioxidant capacity and concluded that most legume seeds ranked in the group with the highest activity (>2000 lmol Trolox equiv./serving). Cardador-Martínez, Loarca-Piñ a, and Oomah (2002) determined that common beans possess high antioxidant activity imparted mainly by phenolics, whereas Seneviratne and Harborne (1992) and Ha et al (2010) observed that seed coats of all Vigna species, including V. unguiculata, contained antioxidants such as procyanidins and prodelphinidin. Plant phenolics are present in the free, ester, and insoluble bound forms.…”
Section: Introductionmentioning
confidence: 99%